Seed mass and germination in Asteraceae species of Argentina - Galindez, Guadalupe (2009)
The effects of seed mass variation on germination percentage, mean time to germinate and light requirements for germination in seven Asteraceae species of Argentina were studied. Germination, mean time to germinate and light requirements were significantly different among species at both 20°C and 25/10°C temperature regimes. In general, larger (> 1.0 mg) and intermediate-mass seeds (≥ 0.1 ≤ 1.0 mg) species showed higher germination, lower mean time to germinate and less light requirement than smaller-mass seeds (< 0.1 mg). However, these responses can vary with the species and temperature regime under which germination is tested. These results could help to explain the field observations for variation in seedling establishment between species and populations studied.